Inactivation of FBXW7/hCDC4-β expression by promoter hypermethylation is associated with favorable prognosis in primary breast cancer - Akhoondi, Shahab (BioMed Central, 2010)
INTRODUCTION: Mutational inactivation of the FBXW7/hCDC4 tumor suppressor gene (TSG) is common in many cancer types, but infrequent in breast cancers. This study investigates the presence and impact of FBXW7/hCDC4 promoter methylation in breast cancer. METHODS: FBXW7/hCDC4-β expression and promoter methylation was assessed in 161 tumors from two independent breast cancer cohorts. Associations between methylation status and clinicopathologic characteristics were assessed by Fisher's exact test. Survival was analyzed using the Kaplan-Meier method in addition to modeling the risk by use of a multivariate proportional hazard (Cox) model adjusting for possible confounders of survival. RESULTS: Methylation of the promoter and loss of mRNA expression was found both in cell lines and primary tumors (43% and 51%, respectively). Using Cox modeling, a trend was found towards decreased hazard ratio (HR) for death in women with methylation of FBXW7/hCDC4-β in both cohorts (HR 0.53 (95% CI 0.23 to 1.23) and HR 0.50 (95% CI 0.23 to 1.08), respectively), despite an association between methylation and high-grade tumors (P = 0.017). Interestingly, in subgroups of patients whose tumors are p53 mutated or lymph-node positive, promoter methylation identified patients with significantly improved survival (P = 0.048 and P = 0.017, respectively). CONCLUSIONS: We demonstrate an alternative mechanism for inactivation of the TSG FBXW7/hCDC4, namely promoter specific methylation. Importantly, in breast cancer, methylation of FBXW7/hCDC4-β is related to favorable prognosis despite its association with poorly differentiated tumors. Future work may define whether FBXW7/hCDC4 methylation is a biomarker of the response to chemotherapy and a target for epigenetic modulation therapy.